2015
DOI: 10.3389/fphys.2015.00355
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of SLC4 Family HCO3- Transporters

Abstract: The solute carrier SLC4 family consists of 10 members, nine of which are HCO3- transporters, including three Na+-independent Cl−/HCO3- exchangers AE1, AE2, and AE3, five Na+-coupled HCO3- transporters NBCe1, NBCe2, NBCn1, NBCn2, and NDCBE, as well as “AE4” whose Na+-dependence remains controversial. The SLC4 HCO3- transporters play critical roles in pH regulation and transepithelial movement of electrolytes with a broad range of demonstrated physiological relevances. Dysfunctions of these transporters are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 192 publications
(337 reference statements)
0
56
0
Order By: Relevance
“…To the best of our knowledge, no studies have reported the modulation of SLC4 members by intracellular Zn 2+ through interactions with the cytoplasmic domain. The cytoplasmic domain of SLC4 transporters is only present in animals, adding to the common perception of an advanced regulatory role of the overall N-terminal cytoplasmic domain in higher organisms 12 . Our data reveal multiple Zn 2+ -binding sites in ntcNDCBE and ntcNCBE, all with affinities in the low micromolar range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no studies have reported the modulation of SLC4 members by intracellular Zn 2+ through interactions with the cytoplasmic domain. The cytoplasmic domain of SLC4 transporters is only present in animals, adding to the common perception of an advanced regulatory role of the overall N-terminal cytoplasmic domain in higher organisms 12 . Our data reveal multiple Zn 2+ -binding sites in ntcNDCBE and ntcNCBE, all with affinities in the low micromolar range.…”
Section: Discussionmentioning
confidence: 99%
“…The primary structure of the isolated cytoplasmic regulatory domains shares lower sequence identity across the SLC4 family, than the transmembrane regions. Based on sequences with either low or high sequence variability, the cytoplasmic domains have been divided into regions referred to as constant regions (CRs) and variable regions (VRs) 12 . The VRs mainly include the different functional and regulatory motifs of SLC4 family members and their isoforms 13 .…”
Section: Introductionmentioning
confidence: 99%
“…They arise from two alternative promotors, three optional structural elements (cassettes I-III), and respective alternative splicing ( Figure S1 C) ( Liu et al., 2013 , Parker and Boron, 2013 , Pushkin et al., 1999 ). SLC4A7 is expressed in several cell types and tissues including brain, heart, and kidney ( Damkier et al., 2007 , Liu et al., 2015 , Pushkin et al., 1999 , Romero et al., 2013 ). Although data on SLC4A7 expression in the immune system are scarce, there is evidence for a specific role in macrophages.…”
Section: Main Textmentioning
confidence: 99%
“…Two genes with known rare variants shared between the proband and the proband's sister are presented in Table II. The first identical mutation in the proband and the proband's sister was on solute carrier family 4 member 1 (SLC4A1; GenBank ID NM_000342.3) which is a band 3 cytoplasmic domain and phosphotransferase/anion transporter (19). A heretogenous missense variant c.388G>A (p.Gly130Arg, rs121912749) in exon 6 of SLC4A1 was observed.…”
Section: Resultsmentioning
confidence: 99%